Cultivating Nurse Competence: The Power of Culture, Sharing, and Motivation: Meningkatkan Kompetensi: Mengungkap Dampak Budaya Organisasi, Berbagi Pengetahuan, dan Motivasi Intrinsik pada Perawat Klinik Rawat Jalan di Rumah Sakit Tipe B - Fahmi Achmadan; Rifdah Abadiyah (Academia Open, 2022)
This quantitative research study investigates the influence of organizational culture, knowledge sharing, and intrinsic motivation on the competence of outpatient clinic nurses at a Type B hospital located in Sidoarjo, Indonesia. A total of 44 respondents participated by completing questionnaires. Multiple linear regression analysis using SPSS version 22 for Windows was employed to analyze the collected data. The results reveal that organizational culture does not significantly impact competence, whereas knowledge sharing and intrinsic motivation positively affect the competence of outpatient clinic nurses. These findings provide valuable insights for healthcare organizations aiming to enhance nurse competence and emphasize the importance of fostering knowledge sharing and intrinsic motivation among nurses. Highlights: Organizational culture: Influence on nurse competence Knowledge sharing: Enhancing nurse competence through collaboration Intrinsic motivation: Fueling nurse competence and performance Keywords: competence, organizational culture, knowledge sharing, intrinsic motivation, outpatient clinic nurses